Volatile Compounds of Pluchea indica Less and Ocimum basillicum Linn Essential Oiland Potency as Antioxidant - PAINI SRI WIDYAWATI; CHRISTOFORA HANNY WIJAYA; PENI SUPRAPTI HARDJOSWORO; DONDIN SAJUTHI (Bogor Agricultural University, Indonesia, 2013)
This research was conducted to identify volatile compounds of pluchea and basil essential oils and their antioxidant capacity to scavenge a DPPH (1,1-diphenyl-2-picrylhidrazyl) free radical and inhibit lipid peroxidation. Essential oil of pluchea and basil leaves was prepared by hydrodistillation method and then their volatile compounds were identified by GC-MS. The volatile compounds in the essential oil of pluchea leaves consist of 66 components with (10S,11S)-Himachala-3-(12)-4-diene (17.13%) made up the highest proportion of volatile compounds. Basil leaves had 70 volatile components in which the major components were (E)-3,7-dimethyl-2,6-octadienal (23.98%) and (Z)- 3,7-dimethyl-2,6-octadienal (17.35%). Total phenol levels in pluchea and basil essential oils were 275 and 209 ppm, respectively. DPPH scavenging activity of the essential oil of pluchea leaves was lower than that of basil leaves, conversely inhibition activity of lipid peroxidation in palm oil of pluchea essential oil was higher than that of basil leaves.